Pergulatan Sejarah dan Isu-Isu Kontemporer dalam Wacana Otoritas Hadits - Jailani, Mohammad (UIN Sunan Kalijaga Yogyakarta, 2022)
The realm of hadith has evolved and expanded to encompass not only the term